Genetic background influences pig responses to porcine reproductive and respiratory syndrome virus - Pei, Yangli; Lin, Chenghong; Li, Hua; Feng, Zheng (Frontiers in Veterinary Science, 2023)
Porcine reproductive and respiratory syndrome virus (PRRSV) is a highly infectious and economically significant virus that causes respiratory and reproductive diseases in pigs. It results in reduced productivity and increased mortality in pigs, causing substantial economic losses in the industry. Understanding the factors affecting pig responses to PRRSV is crucial to develop effective control strategies. Genetic background has emerged as a significant determinant of susceptibility and resistance to PRRSV in pigs. This review provides an overview of the basic infection process of PRRSV in pigs, associated symptoms, underlying immune mechanisms, and roles of noncoding RNA and alternative splicing in PRRSV infection. Moreover, it emphasized breed-specific variations in these aspects that may have implications for individual treatment options.